Analisis Spasial Distribusi Kasus Filariasis Di Provinsi Nusa Tenggara Timur Tahun 2008-2012 - ETY RAHMAWATI; Johanis Jusuf Pitreyadi Sadukh; Oktofianus Sila (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
East Nusa Tenggara Province (NTT) is one of the endemic areas with the number of filariasis cases increasing from year to year. There are two types of filarial worms, Wuchereria bancrofti, and Brugia timori. Filariasis cases in NTT Province up to January 2013 were as many as 925 cases with a prevalence of 0.20 ‰. Research Objectives to determine the distribution of filariasis cases in East Nusa Tenggara Province in 2008 - 2012. Types of Descriptive Research with secondary data study methods. The results of the research data were analyzed descriptively and presented the data using tables and map images. The results of the study are expected to provide information to educational institutions and health agencies regarding the distribution of filariasis cases in East Nusa Tenggara Province in 2008 - 2012. The results showed that there were 12 districts (57%) found filariasis cases in East Nusa Tenggara Province in 2008 - 2012 with a prevalence of 0.02 ‰ - 4.37 ‰. Age> 15 years are the most sufferers (84.93%), and men are the most sufferers (66.31%). Central Sumba Regency, Rote Ndao District, and Alor Regency have mass treatment in total population (100%), and nine districts are still under 85%. To improve the clinical case finding of filariasis, it is necessary to improve the surveillance performance of cases, among others by increasing the discovery and confirmation of cases and conducting refresher training/training for surveillance officers in the area. In the District Health Office, it is necessary to validate the reported case data.